Efficient co-isolation of microvascular endothelial cells and satellite cell-derived myoblasts from human skeletal muscle - Wüst, Rebecca; Terrie, Lisanne; Müntefering, Thomas; Ruck, Tobias; Thorrez, Lieven (Frontiers in Bioengineering and Biotechnology, 2022)
Vascularization of tissue-engineered constructs remains a key challenge in the field of skeletal muscle tissue engineering. One strategy for vascularizing organoids is in vitro pre-vascularization, relying on de novo assembly of undifferentiated endothelial cells into capillaries, a process termed vasculogenesis. In most endothelial cell research to date, human umbilical vein endothelial cells have been used primarily because of their availability. Nevertheless, this endothelial cell type is naturally not occurring in skeletal muscle tissue. Since endothelial cells display a tissue-specific phenotype, it is of interest to use muscle-specific microvascular endothelial cells to study pre-vascularization in skeletal muscle tissue engineering research. Thus far, tissue biopsies had to be processed in two separate protocols to obtain cells from the myogenic and the endothelial compartment. Here, we describe a novel, detailed protocol for the co-isolation of human skeletal muscle microvascular endothelial cells and satellite cell-derived myoblasts. It incorporates an automated mechanical and enzymatic tissue dissociation followed by magnetically activated cell sorting based on a combination of endothelial and skeletal muscle cell markers. Qualitative, quantitative, and functional characterization of the obtained cells is described and demonstrated by representative results. The simultaneous isolation of both cell types from the same donor is advantageous in terms of time efficiency. In addition, it may be the only possible method to isolate both cell types as the amount of tissue biopsy is often limited. The isolation of the two cell types is crucial for further studies to elucidate cell crosstalk in health and disease. Furthermore, the use of muscle-specific microvascular endothelial cells allows a shift towards engineering more physiologically relevant functional tissue, with downstream applications including drug screening and regenerative medicine.